Factors and Reasons That Influenced The Misyar Marriage Phenomenon in Surabaya Urban Communities - Mochamad Rochman Firdian (Journal of Social Science, 2022)
This study aims to analyze the factors and reasons behind the Misyar marriage phenomenon in Surabaya urban communities. The practice of misyar marriage is a marriage in which the husband visits the wife's residence, but the wife is reluctant to move to the husband's residence. In the context of the phenomenon of marriage agreement (a study of the practice of misyar marriage in the urban community of Surabaya), each party also has a different background and purpose. This study used descriptive qualitative studi, it describes in a structured, accurate, and factual manner related to the problems that occur, which include cases of misyar marriage practices in the urban community of Surabaya. The results show that the practice of misyar marriage in the urban community of Surabaya has unique characteristics that are different from the initial form of misyar marriage carried out by the Arab community. Based on the information obtained from the perpetrators and informants, in the practice of misyar marriage in the urban community of Surabaya the factors behind this phenomenon are factors of family social needs, factors of religious understanding, biological factors, life choices factors, socio-cultural factors, and economic factor